Joking about the State: Moral and Aesthetic Food Consumption in the context of Argentina’s post-Covid-19 economic crisis - Andrés Dapuez (Iberoamericana. América Latina - España - Portugal)
In 2021 a group of left-wing protesters wrote “basta de polenta” in letters made of the eponymous grain in front of the Argentine Ministry of Social Development (Ministerio de Desarrollo Social). Ridiculing the government’s paternalistic policy of distributing superfluous free food to the needy became a viral political joke. As news or as a meme, it was largely consumed and commented on through social networks. Indignation and laughter preceded reflections on the state’s moralization of poverty and previous electoral promises to promote red meat consumption among low-income families. Jokes and ironies challenged the “moral economy” promoted by the Frente de Todos (“Everyone’s Front”) government. A state-created image of the poor and one of the government’s moral panics, looting, were ridiculed through polenta jokes. In this way, political and moral practices in relation to crises of consumption were transformed into the consumption of jokes, at the same time that as a right-wing electorate grew.